SPECIFITY OF SLOVENIAN FOLK TALES' TYPE INDEX IN INTERCULTURAL CONTEXT (Philological Studies, 2019)
The monograph’s by Monika Kropej Telban Type index of Slovenian folk tales, animal tales and fables is the first in a series of Slovenian indexes in the European space and place specific Slovenian fairy-tale on multicultural Europe and fairy tale map (Alberus, Apulej, Archilochus, Babrius, Bidpai, Ennius, Aesop, Hesiod, Horace, Phaedrus, Antonius von Pforr, Sachs, Steinhöwel, Burkkhard Waldis et al.). Moreover, it is increasing the academic level of Slovenian folklore and literary studies. The article presents a processed and expanded review of that monograph.
Keywords: ATU index, A. Aarne, S. Thompson, H. J. Uther, M. Kropej Telban